The use of in vitro gas production technique to evaluate molasses supplementation to mulberry (morus alba) and rice straw mixed diets - Dwi Yulistiani; Z.A Jelan; J.B Liang; H Yaakub; N Abdullah (Indonesian Center for Animal Research and Development (ICARD), 2007)
Mulberry foliages have high nutritive value (protein content, digestibility and degradability), therefore it is potential to be used as a supplement to poor quality roughages. The objective of this experiment was to evaluate the effect of addition of fermentable energy in the mixed of mulberry and rice straw basal diet. A control diet consisted of either rice straw (RS) or urea treated rice straw mixed with mulberry foliage (URS) with ratio of 60 : 40%. Treatment was formulated by supplementation of control diet with molasses (as sources of fermentable energy) at 3 levels (5, 10 and 15%). The study was conducted in a 2 x 4 factorial experiment, consisted of 2 levels rice straw (untreated and urea treated) and 4 levels molasses supplementation (control and 3 levels for molasses). Diets were evaluated using in vitro gas production. The fermentation kinetics was determined from the incubation of 200 mg sample during 96 hours. The calculation of the kinetics based on exponential equation P = A+ B (1-e-ct). A shorter gas production test was carried out to determine truly degradable fermented substrates (in vitro true organic matter degradability/IVTOMD) by incubating 500 mg of samples 24 hours. The result showed that there was no significant interaction between rice straw treatment and molasses supplementation on fermentation characteristics, in vitro true dry matter digestibility, fermented substrate and total volatile fatty acid (VFA) production. However there was a significant interaction between rice straw treatment on partitioning factor (PF), gas produced, propionic acid production and ratio between acetic acid and propionic acid. Molasses supplementation significantly (P<0.05) decreased gas production and ratio of acetic to propionic acid, and increase PF, propionic acid production in untreated rice straw mulberry (RSM) basal diet. It is concluded that molasses supplementation to RSM diet decreased gas production and ratio of C2/C3, and increased PF and propionic acid production. Key Words: Mulberry Foliage, Molasses, Rice Straw, In Vitro Gas Production